Galerkin method for the higher dimension Boussinesq equation non linear with integral condition - Draifia, Ala Eddine (University of Eloued جامعة الوادي, 2019)
Abstract-This paper deals with the solvability of a higher dimension mixed non local problem for a Boussinesq equation non linear. Galerkin s method was the main used tool for proving the solvability of the given non local problem.
Working paper.3rd International Conference in Operator Theory, PDE and Applications. April 23-24- 2019. Faculty of Exact Science. Mathematics Department. University of ElOued
Keywords: Boussinesq equation, non local condition, Galerkin s Method